Medicine in the Talmud: natural and supernatural therapies between magic and science - Mokhtarian, Jason Sion (University of California Press, 2021)
Medicine on the margins -- Trends and methods in the study of Talmudic medicine -- Precursors of Talmudic medicine -- Empiricism and efficacy -- Talmudic medicine in its Sasanian context.